(untitled) (LEGAL DIALOGICA, 2025)
The aim of the research is to understand and analyze the rules related to legal protection for workers and to understand the factors that influence work accidents and cause death. Based on the research results, the conclusion obtained is that the rules relating to legal protection for workers who die as a result of work accidents are contained in the Job Creation Law Number 6 of 2023 concerning Job Creation, which is the law that regulates the rights of workers who die as a result of work accidents. . This regulation also aims to provide protection to workers in realizing the welfare of each worker and PP No. 82 of 2019 article 34 contains JKM benefits in the form of Death Compensation to heirs and scholarships for victims’ children. The nominal value for children and wives of victims who died as a result of work accidents is 48 times the wages reported to children or wives and scholarships for 2 children with a maximum figure of 174,000,000.00 starting from kindergarten to university. The factors that cause work accidents and result in workers dying are predominantly human/workforce factors themselves. Abstrak: Tujuan penelitian untuk memahami dan menganalisis aturan yang terkait dengan Perlindungan Hukum terhadap Buruh dan Untuk memahami faktor yang mempengaruhi terjadinya kecelakaan kerja hingga menyebabkan meninggal dunia. Berdasarkan hasil penelitian, maka diperoleh Kesimpulan yaitu Aturan yang terkait dengan Perlindungan Hukum bagi buruh yang meninggal akibat Kecelakaan kerja tercantum dalam Undang-Undang Cipta Kerja Nomor 6 Tahun 2023 Tentang Cipta Kerja menjadi Undang-undang yang mengatur tentang hak buruh yang meninggal dunia akibat kecelakaan kerja. Peraturan tersebut juga bertujuan untuk memberikan pelindungan kepada buruh dalam mewujudkan kesejahteraan setiap tenaga kerja dan PP No.82 Tahun 2019 pasal 34 yang berisi tentang manfaat JKM berupa Santunan Kematian kepada ahli waris dan beasiswa untuk anak korban. Nominal kepada anak dan istri korban yang meninggal akibat kecelakaan kerja yaitu 48 kali upah dari yang dilaporkan kepada anak atau istri dan beasiswa kepada 2 orang anak yang ber-angka maksimum 174.000.000,00 mulai dari TK sampai dengan Perguruan Tinggi. Faktor yang menyebabkan terjadinya kecelakaan kerja hingga mengakibatkan buruh meninggal yaitu dominan karena faktor manusia/tenaga kerja itu sendiri.